Genotypic diversity of Mycobacterium tuberculosis in Buenos Aires, Argentina - Monteserin, Johana (2018)
Fil: Monteserin, Johana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.